Pengendalian Selisih (Gap) antara Actual Processing Time dengan Ideal Processing Time di Pabrik Kelapa Sawit Menggunakan Individual Moving Range (I-MR) Chart - M Hudori; Vina Wulandari (JURNAL CITRA WIDYA EDUKASI, 2022)
This research discusses controlling the gap of Actual Processing Time and Ideal Processing Time in a palm oil mill (PKS). The purpose is to find out how the gap of the two processing times for palm oil in the PKS and how the losses experienced by the company with these conditions. This research uses the individual moving range (I-MR) Chart method. The test is carried out first with the MR-Chart, and will be revised if there is an out-of-control condition. Next will be testing the condition of the time gap with the x-Chart. In the event of an out-of-control condition, a process capability measurement (Cp) will be carried out. The result showed that the PKS studied had poor gap processing time, although the gap that occurred were still within reasonable limits in accordance with the performance of the PKS. However, this condition still results in considerable losses for the company because it has to incur more operational costs than it should.